Factors affecting prognosis in traumatic cerebral contusions: A protocol for a systematic review and meta-analysis - Chao Li; Zhaoyin Su; Shulu Deng; Binhao Zhang; Junlong Qin; Kun Wu; Yanzong Zhao; Yao Liu (PLoS ONE, 2025)
Background Traumatic cerebral contusion (CC) is a severe type of injury among traumatic brain injury (TBI) patients. Individuals with traumatic CC typically exhibit rapid deterioration in their condition, leading to increased mortality rates. Despite this, there is a gap in evidence-based research. This study aims to identify the risk factors associated with adverse outcomes in patients with traumatic CC, with a particular focus on relevant biomarkers. Mortality will be the primary outcome, while the Glasgow Coma Scale (GCS) score will be considered as a secondary outcome. Methods and analysis We intend to conduct a comprehensive search through multiple Chinese and English repositories, covering the duration from the establishment of these databases up to the current era, in order to pinpoint appropriate studies. Additionally, a manual search of the references within the included literature and other pertinent works will be undertaken. The primary endpoint of this study will be the survival status of patients with traumatic brain contusion. Meta-analysis will be executed using STATA 16.0 (Stata Corporation, College Station, TX). Article selection and data extraction will be performed independently by two reviewers. The assessment of bias risks will be conducted via the Cochrane Collaboration’s tool. Depending on the heterogeneity evaluation, either a fixed-effect model or a random-effects model will be applied. Subgroup and sensitivity analyses will be conducted as needed. The examination of publication bias will be carried out, and the quality of evidence for the primary outcomes will be graded. Trial registration number: CRD42023389456